Measurement of peripheral arterial tonometry in patients with diabetic foot ulcers during courses of hyperbaric oxygen treatment - Hedetoft, Morten; Olsen, Niels V; Smidt-Nielsen, Isabel G; Wahl, Anna M; Bergström, Anita; Juul, Anders; Hyldegaard, Ole (Diving and hyperbaric medicine, 2020)
Treatment of diabetic foot ulcers is complex and often protracted. Hyperbaric oxygen treatment (HBOT) improves wound healing in diabetic ulcers and serves as an important adjunct to regular diabetic wound care. Endothelial dysfunction plays a central role in diabetes-related vascular complications and may be evaluated by a non-invasive technique called peripheral arterial tonometry which measures a reactive hyperaemia index (RHI). We hypothesized that endothelial function measured by peripheral arterial tonometry is impaired in diabetic foot ulcer patients and that HBOT might improve endothelial function. Endothelial function was prospectively assessed by peripheral arterial tonometry in 22 subjects with diabetic foot ulcers and 17 subjects without diabetes during courses of HBOT. Endothelial function was evaluated before first (baseline) and 30th treatments, and at 90-day follow-up. Serum insulin growth factor-I (IGF-I) concentrations were determined by immunoassay. Results were compared to 23 healthy subjects. No baseline differences were found in endothelial function between subjects with diabetes, HBOT patients without-diabetes and healthy control subjects (RHI; 1.26, 1.61 and 1.81, respectively). No significant changes in RHI were found in patients with (P = 0.17) or without (P = 0.30) diabetes during courses of HBOT. At 90-day follow-up IGF-I was significantly reduced in the subjects with diabetes (P = 0.001) and unchanged in the group without diabetes (P = 0.99). We found no significant differences in RHI between subjects with diabetic foot ulcers and patients without diabetes, nor improvement in endothelial function assessed by peripheral arterial tonometry during courses of HBOT.